Perceptions of Students, Teachers and Graduates About Civil Aviation Cabin Services ESP Program: An Exploratory Study in Turkey - Mede, Enisa; Koparan, Nergis; Atay, Derin (Springer, 2018)
English for Specific Purposes (ESP) is a movement based on the proposition that language teaching should be tailored to the specific learning and language needs of particular groups of students. In Turkey, the growth of English is striking as it is cultivating students’ English proficiency along with their English competence in specific areas to meet their future needs is given great importance. However, research done for ESP has been limited so far. The present study, therefore, aims to investigate the perceptions of Turkish ESP students, teachers and graduates regarding the English course designed for Aviation Cabin Crew Members. The data were collected by means of semi-structured interviews and analyzed through pattern coding. The results revealed similar perceptions including the three groups of participants’ expectations, experiences, challenges and respective solutions about the development of the existing ESP course which will serve as a reference in designing similar programs to facilitate learning English for specific disciplines.
Keywords: Aviation; Cabin Crew; Language Needs; Learning Needs; Course Evaluation; ESP